Theories of counseling and psychotherapy : an integrative approach - Jones-Smith, Elsie (Los Angeles : SAGE, 2016)
The second edition of theories of counseling and psychotherapy : an integrative approach also breaks new ground in outlining the criteria for what i believe is the fifth force in psychology and psychotherapy - neuroscience
The First force in psychotherapy : psychoanalysis and psychodynamic theories -- The Second force in psychotheraphy : behavior therapy and cognitive therapy -- Part III : The Third force in psychotherapy : existential and humanistic theories -- The Fourth force in psychotherapy : social constructivism and postmodernism -- The Fifth force in psychotherapy : neuroscience and theories of psychotherapy
Includes bibliographical references and index.
Keywords: COUNSELING; PSYCHOTHERAPY; COUNSELING -- CASE STUDIES